The role of nicotinic receptors in alcohol consumption - Helen M. Kamens; Geneva Flarend; William J. Horton (Elsevier, 2023)
The use of alcohol causes significant morbidity and mortality across the globe. Alcohol use disorder (AUD) is defined by the excessive use of this drug despite a negative impact on the individual's life. While there are currently medications available to treat AUD, they have limited efficacy and several side effects. As such, it is essential to continue to look for novel therapeutics. One target for novel therapeutics is nicotinic acetylcholine receptors (nAChRs). Here we systematically review the literature on the involvement of nAChRs in alcohol consumption. Data from both genetic and pharmacology studies provide evidence that nAChRs modulate alcohol intake. Interestingly, pharmacological modulation of all nAChR subtypes examined can decrease alcohol consumption. The reviewed literature demonstrates that nAChRs should continue to be investigated as novel therapeutics for AUD.